التدريب في الملاعب الاصطناعية الخشنة وعلاقته بالإصابات التي يتلقاها عدائي ألعاب القوى - نمرود بشير, (sports creativity, 2025)
Abstract : The study centering on various injuries received by athletics during training in hard floors, whether competitive, recreational, health training and exposure to different types of injuries and the reasons leading to it; also adopted in this research on the descriptive approach which included the analysis and interpretation of the results obtained depending on the necessary measures, including tests the law of proportionality and adequate square test; the researcher used the questionnaire as a tool to gather information, as this study has supported the theoretical background was the references relied upon